Pengembangan Media Focusky Terintegrasi Nilai Agama Untuk Mengembangkan Karakter Disiplin Siswa Sekolah Dasar: Development of Integrated Focusky Media on Religious Values ​​to Develop the Discipline Character of Elementary School Students - Yunita, Irma; Triwoelandari, Retno; Fahri, Muhammad (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study was to find out how the procedure of developing focusky media integrated religious values to develop the character of discipline. The research method used is research and development or Research and Development (R & D) which consists of three stages, namely: preliminary study, model development, model testing. The population used is elementary school students (SD), the sample taken is 5th grade elementary school students. The instruments in this study used observations, student response questionnaires to the media and product assessment questionnaires. Based on the results of the study, the development of integrated focusky media on religious values fulfilled the eligibility criteria with the results of material experts 'assessment by obtaining a feasibility presentation of 84% with a very valid category, the results of language experts' evaluation of 77% with valid categories, the results of media expert evaluations of 93% the category is very valid and the results of the respondent's evaluation are 94.21% with a very valid category. This shows that focusky media development products integrated religious values to develop disciplinary characters worthy of being used in the learning process.